Stripe 82X Data Release 3: Multiwavelength Catalog with New Spectroscopic Redshifts and Black Hole Masses - Stephanie LaMassa; Alessandro Peca; C. Megan Urry; Eilat Glikman; Tonima Tasnim Ananna; Connor Auge; Francesca Civano; Aritra Ghosh; Allison Kirkpatrick; Michael J. Koss; Meredith Powell; Mara Salvato; et al. (The Astrophysical Journal)
We present the third catalog release of the wide-area (31.3 deg ^2 ) Stripe 82 X-ray survey. This catalog combines previously published X-ray source properties with multiwavelength counterparts and photometric redshifts, presents 343 new spectroscopic redshifts, and provides black hole masses for 1297 Type 1 active galactic nuclei (AGN). With spectroscopic redshifts for 3457 out of 6181 Stripe 82X sources, the survey has a spectroscopic completeness of 56%. This completeness rises to 90% when considering the contiguous portions of the Stripe 82X survey with homogeneous X-ray coverage at an optical magnitude limit of r < 22. Within that portion of the survey, 23% of AGN can be considered obscured by being either a Type 2 AGN, reddened ( R − K > 4, Vega), or X-ray obscured with a column density of N _H > 10 ^22 cm ^−2 . Unlike other surveys, there is only an 18% overlap between Type 2 and X-ray obscured AGN. We calculated black hole masses for Type 1 AGN that have Sloan Digital Sky Survey spectra using virial mass estimators calibrated on the H β , Mg ii , H α , and C iv emission lines. We find wide scatter in these black hole mass estimates, indicating that statistical analyses should use black hole masses calculated from the same formula to minimize bias. We find that the AGN with the highest X-ray luminosities are accreting at the highest Eddington ratios, consistent with the picture that most black hole mass accretion happens in the phase when the AGN is luminous ( L _2−10keV > 10 ^45 erg s ^−1 ).